Louis Paul Boon : het literatuur- en kunstkritische werk : IV.2. Vooruit - Boon, Louis Paul; Humbeeck, Kris; Bruinsma, E.; Haagdorens, K. (Antwerpen: Louis Paul Boon-documentatiecentrum, 1997)
"Bezorgd door K. Humbeeck, E. Bruinsma, K. Haagdorens, J. Dierinck & B. Nuyens ; m.m.v. D. de Geest, A.M. Musschoot & Y. T'Sjoen"